HUMAN RESOURCE DEVELOPMENT STRATEGY FOR IMPROVING TEACHER PERFORMANCE: Research in MTs Miftahul Falah and MTs Ciganitri Bandung - Suryadi, Hadi (Journal of Islamicate Studies, 2019)
This research begins with the findings of a preliminary study of the vision and mission of MTs Miftahul Falah and MTs Ciganitri Bandung to improve the quality of human resources continuously and sustainably. This study aims to add the latest research on human resource development planning to improve teacher performance and conduct visual research based on data found in the field in the form of development program planning, development implementation, supporting factors and inhibitors of human resource improvement strategies to improve teacher performance in the two educational institutions. The method used in this research is a descriptive-analytic method with a qualitative approach. The use of human resource management theory is done in the form of adaptation that is applied to teachers as one component in both educational institutions. The primary data source is the madrasa head and deputy madrasa head of curriculum and teachers, secondary data sources come from supporting documentation and other files related to this research. Data was collected through interviews, participatory observation, and study documentation. The data analysis technique used is the documentative narrative analysis. The results of this study indicate that the strategy for developing human resources in the two institutions is carried out by continuously reviewing the vision, mission, and strategies to improve teacher performance. The indicators of teacher performance improvement can be seen from the positive responses from every teacher to the program rolled out by the headmaster from year to year, increasing the number of teachers in teacher professional improvement activities, such as in-house training, workshops, and teachers actively involved in the madrasah teacher working group. Broadly speaking, the factors that influence strategies in improving human resources to improve teacher performance are: First, the factors supporting good leadership from the madrasa head, human capital, and the vision of the institution. The solution to strengthening support is human resources that are continuously improved in the form of the carrying capacity of the madrasa head as the leader in the institution. Second, the inhibiting factors are human resources who do not want to develop, and the madrasa head lacks vision in developing human resources.